Cover Crops for Managing Root-Knot Nematodes - Harsimran K. Gill; Zane Joseph Grabau; Robert McSorley (EDIS)
Cover crops are grown between cash crop cycles or incorporated with cash crops to improve soil fertility and structure, decrease soil erosion, and suppress weeds, insects, nematodes, and other plant pathogens. Cover crop residues can be incorporated as “green manure” to increase soil fertility for the next crop. Cover crops also help to enhance many beneficial organisms and may contribute to carbon sequestration. They help curtail the spread of nematodes because nematodes cannot migrate to another field if a cover crop is not a host to them. Instead, some of them may starve, which helps to manage their population. Fallow soil also helps keep nematode populations lower, but it may lead to erosion and other problems. Many different types of cover crops are adapted for cultivation in the southern United States, including cowpea, sorghum-sudangrass, sunn hemp, marigolds, jointvetch, sesame, grasses, rye, wheat, oats, crimson clover, vetch, lupine, and, of late, legumes.